Impact of Menstrual Function on Hormonal Response to Repeated Bouts of Intense Exercise - Melin, Anna K.; Ritz, Christian; Faber, Jens; Skouby, Sven; Pingel, Jessica; Sundgot-Borgen, Jorunn; Sjödin, Anders; Tornberg, Åsa B. (Frontiers in Physiology, 2019)
Background: Strenous exercise stimulates the hypothalamic-pituitary (HP) axis in order to ensure homeostasis and promote anabolism. Furthermore, exercise stimulates a transient increase in the neurotrophin brain-derived neurotrophic factor (BDNF) suggested to mediate the antidepressant and anxiolytic effects of exercise, and positively correlated with cognitive performance. Athletes with secondary functional hypothalamic amenorrhea (FHA) have been reported to have lower BDNF, and a blunted HP axis respons to exercise as athletes with overtraining syndrome. Aim: The aim of the study was to investigate the hormonal and BDNF responses to a two-bout maximal exercise protocol with four hours of recovery in between in FHA and eumenorrheic (EUM) athletes. Methods: EUM (n=16) and FHA (n=14) endurance athletes were recruited from national teams and competitive clubs. Protocols included gynaecological examination; body composition (DXA); 7-day assessment of energy availability; blood sampling pre and post the two exercises tests. Results: There were no differences between groups in hormonal responses to the first exercise bout. After the second exercise bout IGFBP-3 increased more in FHA compared with EUM athletes (2.1 ± 0.5 vs. 0.6 ± 0.6 μg/L, p=0.048). There were non-significant trends towards higher increase in IGF-1 (39.3 ± 4.3 vs. 28.0 ± 4.6 μg/L, p=0.074), BDNF (96.5 ± 22.9 vs. 34.4 ± 23.5 μg/L, p=0.058), GH to cortisol ratio (0.329 ± 0.010 vs. 0.058 ± 0.010, p=0.082), and decrease in IGF-1 to IGFBP-3 ratio (-2.04 ± 1.2 vs. 0.92 ±1.22, p=0.081) in athletes with FHA compared with EUM athletes. Furthermore, there was a non-significant trend towards a higher increase in prolactin to cortisol ratio in EUM athletes compared with athletes with FHA (0.60 ± 0.15 vs. 0.23 ± 0.15, p=0.071). No differences in the hormonal responses between the two exercise bouts as a result of menstrual function were found. Conclusion: Although there were tendencies towards a more anabolic response to strenuous exercise in EUM athletes, and a more catabolic response in athletes with FHA, no major differences in the hormonal responses between the two exercise bouts as a result of menstrual function were found.